When "a headache is not just a headache": A qualitative examination of parent and child experiences of pain after childhood cancer. Issue 9 (16th July 2019) - Tutelman, Perri R.; Chambers, Christine T.; Urquhart, Robin; Fernandez, Conrad V.; Heathcote, Lauren C.; Noel, Melanie; Flanders, Annette; Guilcher, Gregory M.T.; Schulte, Fiona; Stinson, Jennifer N.; MacLeod, Julia; Stern, Maya
Abstract: Objective: Today, more than 80% of children diagnosed with cancer are expected to survive. Despite the high prevalence of pain associated with the diagnosis and treatment of childhood cancer, there is a limited understanding of how having cancer shapes children's experience and meaning of pain after treatment has ended. This study addresses this gap by exploring childhood cancer survivors' (CCS') experiences of pain from their perspective and the perspective of their parents. Methods: Twenty semi‐structured interviews were completed with CCS (50% female; mean age = 13.20 y, range = 8‐17 y) and their parents (90% mothers). Data were analyzed using interpretive phenomenological analysis. Results: Analyses revealed three superordinate themes present in the data: ( a ) pain is a changed experience after childhood cancer; ( b ) new or ambiguous pains may be interpreted by CCS and parents as a threat of disease recurrence, late effects, or a secondary cancer; and ( c ) pain interpretation occurs within the broader context of how CCS and parents appraise their cancer experience. Parents generally appraised their child's cancer and pain as more threatening and were influential in guiding their child's interpretations. Conclusions: The cancer experience played an important role in shaping CCS' and their parents' experience and interpretation of pain in survivorship. This study provides novel data to inform the development and refinement of new and existing conceptual models of pain and symptom perception after cancer. The results also point to key areas for future investigation and clinical intervention to address the issue of pain in cancer survivorship.